2016
DOI: 10.3390/ijms17122105
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis in Chemistry and Bio-Medical Sciences

Abstract: There is an increasing necessity for multidisciplinary collaborations in molecular science between experimentalists and theoretical scientists, as well as among theoretical scientists from different fields.[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Quantitative structure–activity relationship (QSAR) has been widely used last years in drug discovery and drug design by medicinal chemists [ 7 , 8 ] and in various practical applications [ 9 , 10 ] to provide quantitative analysis of structure and biological activity relationships of compounds. Different QSAR studies were reported to identify important structural features responsible for the biological activity and to develop predictive models for diverse chemicals by different authors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative structure–activity relationship (QSAR) has been widely used last years in drug discovery and drug design by medicinal chemists [ 7 , 8 ] and in various practical applications [ 9 , 10 ] to provide quantitative analysis of structure and biological activity relationships of compounds. Different QSAR studies were reported to identify important structural features responsible for the biological activity and to develop predictive models for diverse chemicals by different authors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%